1995
DOI: 10.1111/j.1365-2958.1995.18050925.x
|View full text |Cite
|
Sign up to set email alerts
|

Ion permeability of the cytoplasmic membrane limits the maximum growth temperature of bacteria and archaea

Abstract: Protons and sodium ions are the most commonly used coupling ions in energy transduction in bacteria and archaea. At their growth temperature, the permeability of the cytoplasmic membrane of thermophilic bacteria to protons is high compared with that of sodium ions. In some thermophiles, sodium is the sole energy-coupling ion. To test whether sodium is the preferred coupling ion at high temperatures, the proton- and sodium permeability was determined in liposomes prepared from lipids isolated from various bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
101
1
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(108 citation statements)
references
References 42 publications
(45 reference statements)
4
101
1
2
Order By: Relevance
“…Previous studies on the proton permeability in archaeal and bacterial membranes have demonstrated that most Bacteria and Archaea adjust the permeability of the cytoplasmic membranes to the growth temperature of the organism (Elferink et al 1994; Van de Vossenberg et al 1995). The proton permeability is maintained at a constant level by regulation of the phospholipid composition of the cell membrane as a function of the growth temperature (Van de Vossenberg et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the proton permeability in archaeal and bacterial membranes have demonstrated that most Bacteria and Archaea adjust the permeability of the cytoplasmic membranes to the growth temperature of the organism (Elferink et al 1994; Van de Vossenberg et al 1995). The proton permeability is maintained at a constant level by regulation of the phospholipid composition of the cell membrane as a function of the growth temperature (Van de Vossenberg et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The proton permeability of the liposomes was measured with the acid-pulse method, monitored with fluorescent probes (Molecular Probes, Leiden, The Netherlands), as described by Nichols and Deamer (1980), Elferink et al (1994), and Van de Vossenberg et al (1995). The probe 8-hydroxypyrene-1,3,6-trisulfonic acid (HPTS) (pyranine, pK a ϭ 7.3) was used for proton permeability measurements between pH 7.0 and 8.0, and SNAFL (Molecular Probes, Leiden, The Netherlands) (pK a ϭ 7.8) at pH 9.0.…”
Section: Proton and Sodium Ion Permeabilitymentioning
confidence: 99%
“…It is interesting that, although bacteria are the predominant prokaryotic domain of life in most environments on the surface of earth, the other prokaryotic domain, the archaea, are very common and even seem to rule the deep subsurface (13,15). The archaea have a selective advantage in that their cell membrane is much less permeable toward passive diffusion of protons or other ions (16). This may enable the archaea to generate an energized membrane with a 100-fold lower energy loss than the bacteria.…”
mentioning
confidence: 99%
“…The EMA treatment optimization results revealed that increasing the dye concentration, the photoactivation time, and the dye incubation time did not result in a higher signal reduction with heat-killed cells. In addition, EMA apparently cannot penetrate through the viable cell membrane; although, different temperatures generate changes in cell membrane fluidity and permeability (Van de Vossenberg et al 1995). Based on the results of the present study, viable -1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 qPCR can be used to determine the viability of C. albicans when heat treatment is used, and the usefulness of this technique for yeast species was confirmed, as demonstrated previously for some wine yeasts (Andorrà et al 2010) and Zygosaccharomyces bailii cells (Rawstorne and Phister 2009).…”
Section: Discussionmentioning
confidence: 99%